2006
DOI: 10.1007/s00167-006-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Is the degree of osteophyte formation associated with the symptoms and functions in the patellofemoral joint in patients undergoing total knee arthroplasty?

Abstract: Osteophyte formation and loss of articular cartilage are the main pathologic features of osteoarthritis in the patellofemoral joint. The goal of this study was to determine whether the degree of osteophyte formation was associated with the degree of cartilage loss and the patellofemoral symptoms and functions in osteoarthritic patients undergoing total knee arthroplasty (TKA). We evaluated 71 knees in 54 consecutive patients who underwent TKA under the diagnosis of osteoarthritis. The degree of patellofemoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…Our previous intra-operative study of patients undergoing TKR for advanced OA found no statistically significant association between the extent of osteophyte formation and anterior knee pain and patellofemoral functional disability. 24 The reason for the discordance between our studies and those by Cicuttini et al 10 and Lanyon et al 11 is not clear, but may reflect differences in the patient populations which were studied. In the study by Cicuttini et al, 10 only 24.2% of knees had evidence of osteophyte formation, and Lanyon et al 11 found that 215 of 452 knees (47.6%) had no radiological evidence of osteophytes.…”
Section: Discussioncontrasting
confidence: 83%
“…Our previous intra-operative study of patients undergoing TKR for advanced OA found no statistically significant association between the extent of osteophyte formation and anterior knee pain and patellofemoral functional disability. 24 The reason for the discordance between our studies and those by Cicuttini et al 10 and Lanyon et al 11 is not clear, but may reflect differences in the patient populations which were studied. In the study by Cicuttini et al, 10 only 24.2% of knees had evidence of osteophyte formation, and Lanyon et al 11 found that 215 of 452 knees (47.6%) had no radiological evidence of osteophytes.…”
Section: Discussioncontrasting
confidence: 83%
“…The relationship between the development of osteophytosis and cartilage damage remains unclear in the process of osteoarthritis, with conflicting results in different animal models 8,26 and in humans 27,28 . In the present study, the lower correlation seen on MRI compared with CT between osteophytosis and cartilage damage scores could be linked to the fact that grade 1 osteophytes were more often suspected with MRI.…”
Section: Discussionmentioning
confidence: 52%
“…Another study showed that radiographic changes of patellofemoral osteoarthritis do not correlate with patellofemoral symptoms. 27 Indeed, addressing degenerative articular surface by resurfacing the patella has not universally resolved patellofemoral symptoms. 28,29 Although in many cases we cannot identify the specific cause, pain after TKA has been shown to be associated with certain patient factors.…”
Section: Anterior Knee Painmentioning
confidence: 99%